Wandlungen der Bevölkerungsstruktur und der Bevölkerungsbewegungen im südmarokkanischen Oasengebiet - Pletsch, Alfred (ERDKUNDE, 1972)
The change in rural and nomadic life, characteristic of post-colonial times in the semi-arid and arid regions of the world, has proceeded at an extraordinary speed in the oasis area of south-Morocco. The decline of the traditional hierarchy in the social and population structure has resulted in two characteristic phenomena: the rural exodus from the oases to towns in the north of the country (particularly Casablanca), and the sedentarization of nomads in the oases. Thus an exchange of population within the oases results, completely disrupting the demographic situation which shows an emigration from the oases of 15 to 25% of the population within the last 10 years. Concomitantly, population has increased in the order of 2,5% p. a. The population increase however is not the result of higher birthrate, but is principally the influx of sedentary nomads, largley compensating for the emigration of rural population. This appears very clearly by analysing the population movement in different settlements. In almost every village (ksor) populated by people unfavourably placed within the social hierarchy (e. g. the Draoua) population decreases remarkably, while in ksor populated by sedentary or near sedentary nomads, demographic development is positive. For the emigrating population of the oases as well as for sedentary nomads, the change in living conditions evokes considerable problems. Emigrants often represent the inhabitants of the 'bidonvilles' in the towns, while the former nomads become the proletariat of the oases, being neither able nor willing to work in the fields with their own hands. One of the ways to overcome these difficulties seems to be the expansion of economic development to the regions, thus creating possibilities of participation in economic and technical progress within the traditional environment of the population of the desert confines.